1986
DOI: 10.1007/bf00046429
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the immunobiology of the skin. Implications for cutaneous malignancies

Abstract: Recent advances in cutaneous immunobiology have led to the realization that skin is an important and unique immunologic organ. Studies on the immunobiology of skin cancers induced by ultraviolet radiation indicate that immune mechanisms can play a crucial role in the development of cutaneous tumors. This paper summarizes the evidence linking skin and the immune system and discusses current hypotheses concerning the mechanisms by which UV radiation interferes with cutaneous immunity. The significance of these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…As is evident from Figures 2 and 3, the magnitude and the range of protection against lethal virus infection associated with S.C. injection of DHEA were considerably greater than when DHEA was fed in the diet. Recent reports show that the skin may have unique immune functions [Romerdahl, 1986;Streilein, 19831. Indeed the skin is known to contain a population of cutaneous immune cells, which includes the epidermal Langerhans cells and keratinocytes that produce an epidermal thymocyte-activating factor, similar to IL-1 [Sauder, 19841; in the murine system the Thy-lC dendritic epidermal cell.…”
Section: Discussionmentioning
confidence: 99%
“…As is evident from Figures 2 and 3, the magnitude and the range of protection against lethal virus infection associated with S.C. injection of DHEA were considerably greater than when DHEA was fed in the diet. Recent reports show that the skin may have unique immune functions [Romerdahl, 1986;Streilein, 19831. Indeed the skin is known to contain a population of cutaneous immune cells, which includes the epidermal Langerhans cells and keratinocytes that produce an epidermal thymocyte-activating factor, similar to IL-1 [Sauder, 19841; in the murine system the Thy-lC dendritic epidermal cell.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of chemically induced melanoma in mice can be enhanced by treatment with tumor-promoting agents such as croton oil. Studies dating back to 1963 have demonstrated that UV radiation could be used in combination with chemical treatment to induce melanoma in mice, but could not act as a complete carcinogen (Epstein et al, 1967;Romerdahl et al, 1989;Husain et al, 1991).…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Exposure to solar ultraviolet radiation, particularly ultraviolet B (UVB), is the predominant cause of most skin cancers acting through mechanisms of DNA damage (either directly or via free-radical generation) and immune system inhibition [2, 3]. The development of skin cancer is also linked to several patient characteristics, including fair skin, light hair and eye colour, the tendency to burn rather than tan, and family history [2].…”
Section: Introductionmentioning
confidence: 99%